FACTORS AFFECTING THE SUCCESS OF INCLUSIVE BUSINESSES OF CASSAVA FARMER IN SUPPORTING FOOD SECURITY AND FARMER WELFARE - Yayu Ulfah Marliani; Alghif Aruni Nur Rukman (Universitas Sebelas Maret, 2025)
The inclusive business model places farmers involved in the cassava value chain thereby providing market opportunities for farmers. The success of inclusive business is expected to increase food security and balance village development, which will have a major impact on efforts to improve the welfare of cassava farmers. The objectives of this research are analyzing the factors that influence the success of cassava farmers' inclusive businesses. The research method used is a quantitative method, the data used is primary data obtained through structured interviews using questionnaires given to 120 respondents, while secondary data comes from literature studies that are relevant to the research. The data obtained will be analyzed based on its objectives, SEM analysis. The Result is factor that most indirectly influences inclusive business is farmers' motivation towards adopting innovation and technology. Meanwhile, the variables that have a direct influence are the adoption of technological innovation, partnerships, financial access and the role of government.